2012 IEEE 62nd Electronic Components and Technology Conference 2012
DOI: 10.1109/ectc.2012.6248975
|View full text |Cite
|
Sign up to set email alerts
|

Cu wire and Pd-Cu wire package reliability and molding compounds

Abstract: Cu wire is drastically replacing Au wire due to surge of Au price. However, Cu wire package has poorer humidity reliability than Au wire package. Although Pd coated Cu wire package could show better humidity reliability than Cu wire, it is still worse than Au. Enough information regarding failure mechanism was not available. For failure analysis, x-section has been widely used to identify the Cu/Al IMC after failure. However, the x-section is the results of corrosion reaction and doesn't show the IMC status be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…These results suggest that IMC compositions are: Cu 9 Al 4 for IMC I; Cu 3 Al 2 for IMC II; and CuAl for IMC III. Cu 3 Al 2 was also found by Abe et al [10] as noted earlier. The similar IMC formation in this study and Abe's study may be attributed to the similarity in the composition of Al layer which included Cu.…”
Section: Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…These results suggest that IMC compositions are: Cu 9 Al 4 for IMC I; Cu 3 Al 2 for IMC II; and CuAl for IMC III. Cu 3 Al 2 was also found by Abe et al [10] as noted earlier. The similar IMC formation in this study and Abe's study may be attributed to the similarity in the composition of Al layer which included Cu.…”
Section: Methodssupporting
confidence: 80%
“…However, some other studies report that only Cu 9 Al 4 will be added to the CuAl 2 [9]. Abe et al claimed that they identified Cu 3 Al 2 and CuAl while the initial layers were Cu and AlSiCu [10]. Therefore, the understanding of the sequence of IMC phase transformations at the Cu/Al bonds remains incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…EDS analysis at Point 2 showed absence of Clion as corrosion only occurs at the Cu/Al IMC layer. Due to the uneven distribution of Cu/Al IMC and insufficient coverage percentage, this eventually results in many vacancies that will attract reaction with Clion [1], thus causing Cell 1 to fail biased HAST test. To understand the effects of the wafer lot variation that may cause a difference in Cu/Al IMC formation between Cell 1 and Cell 2, further SEM analysis was carried out on the bond pads.…”
Section: Experimental and Resultsmentioning
confidence: 99%
“…[1,2] One of the major corrosives in industrial products is the chlorine content of epoxy molding compound (EMC). [3,4] Many literature have been reported that the Cu wire bonding suffered chlorine ion attack on Cu-Al IMC after thermal annealing, pressure cooker test (PCT), highly accelerated stress test (HAST) or biased-HAST. [5,6,7] In Cu-Al binary system, five intermetallic phases could form during 300°C.…”
Section: Introductionmentioning
confidence: 99%